2000
DOI: 10.1046/j.1365-2168.2000.01383-9.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an EORTC module to improve quality of life assessment in patients with gastric cancer

Abstract: AIMS: The benefit of extended lymphadenectomy in patients with squamous cell carcinoma of the oesophagus is established, but there is little evidence to support this in patients with adenocarcinoma. The aim of this study was to investigate the extent of lymphatic spread of oesophageal adenocarcinomas, and particularly the proximal spread in tumours located in the mid thorax. METHODS: Twenty-six consecutive patients with tumours arising between 29 and 35 cm from the incisor teeth underwent three-stage oesophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…For this purpose, existing general-purpose disease or symptom specific QOL questionnaires, such as GSRS[26,31,32], Gastrointestinal Quality of Life Index[12,33] and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire; EORTC QLQ-C30 + QLQ-STO22[10,13,18,19,21,34-36], which were established for other purposes and had verified reliability and validity, have been mainly used, because there have been no established questionnaires specified for the postgastrectomy evaluation. However, these questionnaires are likely to be inadequate for the clinical evaluation of postgastrectomy patients, because they do not contain “dumping” and/or “meal-related distress”, which are symptoms that are well-recognized as significantly affecting the postoperative QOL of gastrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, existing general-purpose disease or symptom specific QOL questionnaires, such as GSRS[26,31,32], Gastrointestinal Quality of Life Index[12,33] and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire; EORTC QLQ-C30 + QLQ-STO22[10,13,18,19,21,34-36], which were established for other purposes and had verified reliability and validity, have been mainly used, because there have been no established questionnaires specified for the postgastrectomy evaluation. However, these questionnaires are likely to be inadequate for the clinical evaluation of postgastrectomy patients, because they do not contain “dumping” and/or “meal-related distress”, which are symptoms that are well-recognized as significantly affecting the postoperative QOL of gastrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients, who showed partial responses or better, were treated with radiation therapy at a total dose of 40.0 Gy. At least one year after the completion of radiotherapy, patients filled out the EORTC Quality of Life Questionnaire including questions specific for stomach cancer (QLQ-C30-STO22), which included five functional scales, one global scale, nine general symptom scales, and eight stomach-related symptom scales [11]. The raw scores of the global scale (QL) and five functional scales for physical functioning (PF), role functioning (RF), emotional functioning (EF), cognitive functioning (CF), and social functioning (SF)-were linearly transformed to a scale from 0 to 100.…”
Section: Methodsmentioning
confidence: 99%
“…The results of these studies have found that receiving feedback about patients' symptoms and quality of life increased physician-patient communication around specific quality of life areas in general, but providing feedback to clinicians did not increase patients' satisfaction with the clinical encounter [12,47]. This may be explained by the fact that quality of life measures focus on either general domains of functioning or specific symptoms such as pain and anxiety but do not relate these to specific patient concerns such as lack of support from family or friends or the amount of information patients have about aspects of the illness compared to what they desire [11,24,48].…”
mentioning
confidence: 94%